The role of controlling shareholders in influencing firm efficiency: a case of Taiwanese electronics firms - Irene, Wei Kiong Ting; Norazlin, Ahmad; Gurrib, Ikhlaas; Bhaskaran, Rajesh Kumar (Inderscience Enterprises Ltd., 2022)
his study examines how controlling shareholders affected efficiency in Taiwanese electronics firms for the period of 2005-2017. This study measures firm efficiency using a dynamic data envelopment analysis model, which returns scores ranging from zero (not efficient) to one (efficient). Our regression results find that controlling shareholders' levels of shareholdings have significant negative effects on firm efficiency when their shareholding levels are low. However, there is a positive relationship between controlling shareholders' levels of shareholding and firm efficiency when the percentage of their shareholdings is high. These nonlinear results are also confirmed when we use board seat control rights held by the controlling shareholders. This study contributes to the field of corporate governance, specifically in the application of agency theory related to principal-principal relationships. Overall, findings suggest policy-makers should not consider solely controlling shareholders' levels of shareholdings, but also their board seat control rights.